Pengaruh Liquidity Shock, Market Risk, dan Abnormal Trading Volume terhadap Return Saham (Studi pada Sektor Energi) - Sinthia Dewi; Ilzar Daud; Anggraini Syahputri; Giriati Giriati; Anwar Azazi (Lembaga Komunitas Informasi Teknologi Aceh (KITA), Indonesia, 2026)
The Indonesian energy sector has exhibited significant fluctuations following the energy crisis triggered by global geopolitical instability and post-pandemic demand shocks. This study aims to analyze the influence of Liquidity Shock, Market Risk, and Abnormal Trading Volume on the stock returns of companies listed in the Energy Sectorin Indonesia. This research employs a quantitative approach utilizing secondary data spanning from January 2022 to December 2024. Samples were selected using a purposive sampling technique, and the data were analyzed using a multiple linear regression model. The results of this study indicate that (1) Simultaneously, Liquidity Shock, Market Risk, and Abnormal Trading Volume significantly influence stock returns. (2) Partially, Liquidity Shock and Abnormal Trading Volume have a positive influence and serve as key factors in determining stock returns, whereas Market Risk is proven to have a significant negative impact on stock returns.